The transcriptomic basis of oviposition behaviour in the parasitoid wasp Nasonia vitripennis. - Bart A Pannebakker; Urmi Trivedi; Mark L Blaxter; Rebekah Watt; David M Shuker (PLoS ONE)
Linking behavioural phenotypes to their underlying genotypes is crucial for uncovering the mechanisms that underpin behaviour and for understanding the origins and maintenance of genetic variation in behaviour. Recently, interest has begun to focus on the transcriptome as a route for identifying genes and gene pathways associated with behaviour. For many behavioural traits studied at the phenotypic level, we have little or no idea of where to start searching for "candidate" genes: the transcriptome provides such a starting point. Here we consider transcriptomic changes associated with oviposition in the parasitoid wasp Nasonia vitripennis. Oviposition is a key behaviour for parasitoids, as females are faced with a variety of decisions that will impact offspring fitness. These include choosing between hosts of differing quality, as well as making decisions regarding clutch size and offspring sex ratio. We compared the whole-body transcriptomes of resting or ovipositing female Nasonia using a "DeepSAGE" gene expression approach on the Illumina sequencing platform. We identified 332 tags that were significantly differentially expressed between the two treatments, with 77% of the changes associated with greater expression in resting females. Oviposition therefore appears to focus gene expression away from a number of physiological processes, with gene ontologies suggesting that aspects of metabolism may be down-regulated during egg-laying. Nine of the most abundant differentially expressed tags showed greater expression in ovipositing females though, including the genes purity-of-essence (associated with behavioural phenotypes in Drosophila) and glucose dehydrogenase (GLD). The GLD protein has been implicated in sperm storage and release in Drosophila and so provides a possible candidate for the control of sex allocation by female Nasonia during oviposition. Oviposition in Nasonia therefore clearly modifies the transcriptome, providing a starting point for the genetic dissection of oviposition.